Antithrombotic Therapy in Patients with Recent Stroke and Atrial Fibrillation - Saberwal, Bunny; Ioannou, Adam; Lim, Wei Y.; Beirne, Anne-Marie; Chow, Anthony W.; Tousoulis, Dimitris; Ahsan, Syed; Papageorgiou, Nikolaos (Current Pharmaceutical Design, 2020)
Atrial fibrillation (AF) is a common arrhythmia which carries a significant risk of stroke. Secondary prevention, particularly in the acute phase of stroke with anti-thrombotic therapy, has not been validated. The aim of this review is to evaluate the available evidence on the use of antithrombotic therapy in patients with recent stroke who have AF, and suggest a treatment algorithm for the various time points, taking into account both the bleeding and thrombosis risks posed at each stage.
Keywords: anticoagulation